Glycogenes in Oncofetal Chondroitin Sulfate Biosynthesis are Differently Expressed and Correlated With Immune Response in Placenta and Colorectal Cancer - Wu, Zi-Yi; He, Yong-Qiao; Wang, Tong-Min; Yang, Da-Wei; Li, Dan-Hua; Deng, Chang-Mi; Cao, Lian-Jing; Zhang, Jiang-Bo; Xue, Wen-Qiong; Jia, Wei-Hua (Frontiers in Cell and Developmental Biology, 2021)
Oncofetal chondroitin sulfate expression plays an important role in the development of tumors and the pathogenesis of malaria in pregnancy. However, the biosynthesis and functions of these chondroitin sulfates, particularly the tissue-specific regulation either in tumors or placenta, have not been fully elucidated. Here, by examining the glycogenes availability in chondroitin sulfate biosynthesis such as xylosytransferase, chondroitin synthase, sulfotransferase, and epimerase, the conserved or differential CS glycosylation in normal, colorectal cancer (CRC), and placenta tissue were predicted. We found that the expression of seven chondroitin sulfate biosynthetic enzymes, namely B4GALT7, B3GALT6, B3GAT3, CHSY3, CHSY1, CHPF, and CHPF2, were significantly increased, while four other enzymes (XYLT1, CHST7, CHST15, and UST) were decreased in the colon adenocarcinoma (COAD) and rectum adenocarcinoma (READ) patients. In the human placenta, where the distinct chondroitin sulfate is specifically bound with VAR2CSA on Plasmodium parasite-infected RBC, eight chondroitin sulfate biosynthesis enzymes (CSGALNACT1, CSGALNACT2, CHSY3, CHSY1, CHPF, DSE, CHST11, and CHST3) were significantly higher than the normal colon tissue. The similarly up-regulated chondroitin synthases (CHSY1, CHSY3, and CHPF) in both cancer tissue and human placenta indicate an important role of the proteoglycan CS chains length for Plasmodium falciparum VAR2CSA protein binding. Interestingly, twelve highly expressed chondroitin sulfate enzymes were significantly correlated to worse outcomes (prognosis) in both COAD and READ. Furthermore, we showed that the levels of chondroitin sulfate enzymes are significantly correlated with the expression of immuno-regulators and immune infiltration levels in CRCs and placenta, and involved in multiple essential pathways, such as extracellular matrix organization, epithelial-mesenchymal transition, and cell adhesion. Our study provides novel insights into the oncofetal chondroitin sulfate biosynthesis regulation and identifies promising targets and biomarkers of immunotherapy for CRC and malaria in pregnancy.